John Buridan, Quaestiones super octo libros Physicorum Aristotelis (secundum ultimam lecturam) Libri V-VIII - Buridan, John (Late Antiquity and Medieval Studies E-Books Online, Collection 2024., 2024)
John Buridan (d.ca. 1360) was one of the most talented and influential philosophers of the later Middle Ages. He spent his career as a master in the Arts Faculty at the University of Paris, producing commentaries and independent treatises on logic, metaphysics, natural philosophy, and ethics. His Questions Commentary on the eight books of Aristotle's Physics is the most important witness to Buridan's teachings in the field of natural philosophy. The commentary was widely read during the later Middle Ages and the Renaissance. This volume presents the first critical edition of books V-VIII of the final redaction of Buridan's Questions Commentary on the Physics. The critical edition of the Latin text is accompanied by a detailed guide to the contents of Buridan's questions.